2013
DOI: 10.5966/sctm.2013-0097
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Stem/Progenitor Cells for Renal Tissue Repair: Current Knowledge and Perspectives

Abstract: The kidney is a specialized low-regenerative organ with several different types of cellular lineages; however, the identity of renal stem/progenitor cells with nephrogenic potential and their preferred niche(s) are largely unknown and debated. Most of the therapeutic approaches to kidney regeneration are based on administration of cells proven to enhance intrinsic reparative capabilities of the kidney. Endogenous or exogenous cells of different sources were tested in rodent models of ischemia-reperfusion, acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 99 publications
(132 reference statements)
0
38
0
2
Order By: Relevance
“…Concerning adult mammal kidney, there are lots of evidences that suggest existence of renal progenitor system [12][13][14][15][16][17][18][19] . Collectively, these results suggest the potential role of adult stem-like cells in kidney for practical clinical treatment of kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning adult mammal kidney, there are lots of evidences that suggest existence of renal progenitor system [12][13][14][15][16][17][18][19] . Collectively, these results suggest the potential role of adult stem-like cells in kidney for practical clinical treatment of kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since the commonly used adult MSCs derived from tissues have limited abilities in proliferation, secreting bioactive factors and immunomodulation, an alternate source of MSCs is in need. The hiPSC-derived MSCs was found to be a potential source of MSCs because the cells exhibited better survival, proliferation and differentiations potentials [11,12,[14][15][16]. More importantly, several studies showed that hiPSCs-MSCs had hepatoprotective effects in hepatic I/R injury [13,36].…”
Section: Discussionmentioning
confidence: 99%
“…They can divide to replenish dying cells and regenerate damaged tissues, and are considered a powerful tool in regenerative medicine (1)(2)(3). Adult stem cells are thought to be found throughout the body.…”
Section: Introductionmentioning
confidence: 99%